Cultural Volunteering of University Students: Assessment of Participation Experience and Potential for Development - M. V. Pevnaya; A. A. Drozdova (Moscow Polytechnic University, 2022)
Russian universities in recent years are increasingly positioned as centers for the development of Russian regions. As part of their third mission, universities are beginning to be included in the socio-cultural development of the territories. In these processes, student social initiatives and sociocultural projects with their participation are playing an increasingly important role both for the students themselves and their self-realization, and for the Russian regions in the context of increasing their sustainability. The article was based on the materials of two studies: monitoring of the students of the Sverdlovsk region and a survey of the youth of the Sverdlovsk region, implemented in 2020. The authors explore the experience of social participation of university students in the Sverdlovsk region, their involvement in the practice of volunteering in the cultural sphere. The purpose of this article is to characterize the volunteer experience of students in the field of culture, to assess the potential of youth cultural volunteering in the context of solving urgent problems of universities as regional development centers. The authors record an increase in the proportion of students involved in volunteering on a regular basis, with a sufficiently large number of those who, after a one-time participation, are not ready to help in specific volunteer practices. The article deals with groups of students with and without experience of volunteering in the field of culture. The authors prove that students with experience in cultural volunteering are more interested in it and are really involved in the cultural life of their cities. The potential for the development of volunteer activity among a wider range of students lies in the increased interest of young people in major cultural events. The social participation of students in the eventful cultural agenda of cities and regions can increase the competencies of young professionals that are in demand, while it works to form the social responsibility of universities. The identified characteristics of the cultural volunteering of youth in the Sverdlovsk region are also inherent in other Russian regions.